JOSÉ LOUSTAU (1889-1964): PYCHOSOCIOBIOLOGY AND ETHOLOGY CONTRIBUTIONS - Quiñones Vidal, Elena; Romero Medina, Agustín; Pedraja Linares, María José; Vera Sánchez, Miguel (Anales de Psicología / Annals of Psychology)
In this paper, a review of intellectual and academic biography of Jose Loustau (1889-1964), professor of biology and Rector of Murcia University for many years is presented. His contributions to the psychosociobiology and the etology is specially emphasized.